How Corporations Kill Off Sports Fans : Examining the Threats Corporate Sponsorships Pose to Team Identification - Virta, Oili (My University, 2024)
The sports industry thrives on the passionate connection between fans and their favorite teams, a relationship that extends beyond the games themselves and creates lucrative opportunities for corporate sponsorships. These sponsorships aim to leverage the positive associations fans have with their teams, benefiting both sponsors and sports organizations. However, the potential threats corporate sponsorships may pose to team identification remain underexplored. This thesis addresses this research gap by answering the following research question: what threats can corporate sponsorships pose to team identification? This thesis is a literature review. Grounded in social identity theory and self-categorization theory, this study conceptualizes team identification as a vital social identity that provides individuals with self-esteem and builds inter- and intragroup relationships. When team identification fails to meet these psychological needs, its significance may diminish, or it may even be replaced. Utilizing identity threat theory and the concept of sponsor moral appropriateness, the thesis categorizes sponsorship-induced identity threats relating to self-esteem as well as intra-and intergroup perception into three types: categorization threat, distinctiveness threat, and value threat. The findings reveal that categorization threat stems from unwanted stereotypes and associations transferred from the sponsor, primarily affecting individuals with low team identification. Distinctiveness threat arises when a sponsor simultaneously supports multiple teams, diminishing the unique value of team identification. Lastly, value threat occurs when a sponsor's negative publicity or poor corporate social responsibility practices devalue the team identification. This research contributes to academic discussion by defining the nuanced ways corporate sponsorships influence team identification and providing practical insights for sponsors and sports organizations. This thesis also validates the importance of future research into the subject. Limitations of this study include its theoretical nature and reliance on parallel literature rather than empirical data, suggesting future research should validate these findings through qualitative or quantitative methods.
Keywords: Team identification, Sports sponsorship, Identity threat, Sponsor moral appropriateness